EEG as a neural measure of hypoxia-related impairment - Otto, Stephanie R.; Borden, Cammi K.; McHail, Daniel G.; Blacker, Kara J. (Frontiers in Cognition, 2025)
Ambient oxygen decreases with increasing altitude, which poses a primary threat to aviators known as hypoxic hypoxia. Decades of research have shown that hypoxia impairs cognition, but the neurophysiological bases for these effects remain poorly understood. Recent advances in neuroscience have permitted non-invasive observation of neural activity under controlled hypoxia exposures and have begun to uncover how the brain responds to hypoxia. Electroencephalography (EEG) in particular has been used to explore how electrical activity produced by networks of cortical neurons changes under hypoxia. Here we review studies that have explored how hypoxia affects prominent EEG brain rhythms as well as responses to specific events or stimuli in the time and frequency domains. Experimental conditions have varied widely, including whether hypoxia exposures were normobaric or hypobaric and the range of equivalent altitudes and durations of exposures. Collectively, these studies have accumulated support for a variety of candidate neural markers of hypoxia impairment spanning sensory and cognitive domains. Continued research will build on these findings to leverage emerging technologies in neuroscience and further our understanding of how hypoxia affects cognition and associated neural activity.